(untitled) (Itinera, 2018)
This paper aims to clarify the contrasted public response to Romeo Castellucci’s works, analysing particularly his work the Oresteia (2015) in the light of actual philosophic and scientific researches about hypnosis. Hypnosis, in fact, may provides us with the tools to understand the scenic processes which may induce a state of trance-like in the spectator and more generally the emotional path, between shock, hypnosis and distance, proposed by the images on stage.